Atenção primária à saúde: estrutura das unidades como componente da atenção à saúde Primary health care: the structure of units as a component of health care - Bárbara Laisa Alves Moura; Renata Castro da Cunha; Ana Carla Freitas Fonseca; Rosana Aquino; Maria Guadalupe Medina; Ana Luiza Queiroz Vilasbôas; Aline Lima Xavier; Amanda Fortes Costa (Instituto Materno Infantil de Pernambuco, 2010)
OBJETIVOS: avaliar a estrutura das unidades de saúde da atenção primária de dois municípios, comparando as unidades de saúde da família (USF) e as unidades de saúde convencionais (USC). MÉTODOS: estudo transversal, quantitativo, utilizou entrevistas estruturadas e observação da rotina de trabalho das equipes como técnica de coleta de dados. Foram avaliados três componentes: ambiente físico, recurso material e pessoal. RESULTADOS: os achados evidenciaram deficiências estruturais nos três componentes, mais, onde os itens avaliados foram observados em menos de 70,0% das USF. Nos municípios, menos de 50% das unidades possuíam equipamentos básicos. No município A, todas ESF contavam com médicos e enfermeiros e, no município B, 27,3% das ESF estavam sem médico. Ressaltam-se as deficiências que comprometem a biossegurança dos procedimentos e a ausência de estruturas que favorecem o desenvolvimento de intervenções coletivas, necessárias à mudança do modelo assistencial na perspectiva da vigilância da saúde. CONCLUSÕES: embora as redes causais que ligam a estrutura dos serviços de saúde aos seus efeitos sejam complexas e envolvam diversos fatores, os achados do estudo reiteram a necessidade de valorização dos componentes estruturais na avaliação e gestão de saúde. OBJECTIVES: to assess the structure of the primary health care units in two municipalities, comparing the Family Health Units(FHU) and the conventional units. METHODS: a quantitative cross-sectional study was carried out using structured interviews and observation of the work routine of the teams as data collection techniques. Three components were evaluated: the physical environment, material resources, and staff. RESULTS: the findings provided evidence of structural shortcomings in all three components, these being more serious in the Family Health Units. The shortcomings in terms of physical structure were more serious in municipality B, where the items under evaluation were fund in less than 70% of FHUs. In both municipalities, less than 50% of units had basic equipment. In municipality A, all the conventional units had doctors and nurses, while in municipality B, 27.3% of FHUs had no doctor. Shortcomings were revealed that jeopardize biosafety and there was an absence of structures that favor the development of the kind of collective intervention that is necessary for changing the model of care by placing more emphasis on health surveillance. CONCLUSIONS: although the chains of causation that link the structure of health services to their effects are complex and involve various factors, the study findings reiterate the need for more attention to be paid to structural components when evaluating health management.